ETNOMATEMATIKA GERABAH BAYAT DESA MELIKAN KLATEN SEBAGAI BAHAN PEMBELAJARAN MATEMATIKA - Suryandari, Nurlayli Dewi; Setiawan, Toto Bara; Sunardi, S; Setiawani, Susi; Yudianto, Erfan (Kadikma, 2018)
Abstract. The purpose of this study was to explore ethnomatematics on Bayat pottery, production of Bayat Pottery and produce student teaching materials in the form of test packages. This research is qualitative research with ethnographic approaches. The methods of data collection used are observation and interview. 3 people were chosen as research subjects. The ethnomatematics include counting activities, numerical activities, and measuring activities. This study focused on determining the amount of base material for making mixtures or lempung, determining the size of the pottery, determining the ratio of the diameter of the base and lid, determining the shape. Mathematical concepts that emerge are the concept of direct proportion, number sequence, similarity, congruence, and space. Keywords: ethnomatematics, bayat pottery, teaching materials.